Business Process Modelling in Middleware Application Development: Improving Business Processes through Business Process Modelling (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Business Process Modelling (BPM) is a management discipline aimed at describing and managing the business processes in an organization Development. The goal of Business Process Modelling is to achieve the organization’s objectives by aligning the business processes with these objectives and to continually improve these Middleware Development processes. This study proposes an evaluation method for Business Process Modelling. This method will be developing by creating a framework on Business Process Modelling by analyzing the state of the literature regarding Business Process Modelling. This framework contains literature and criteria that have been extracted from this literature. The evaluation method itself consists of a selection of the framework’s criteria, a case, information on how to use the criteria when evaluating the BPM products and a rating method which allows quantification of the evaluation. Most organisations are working hard to improve their performance and to achieve competitive advantage over their rivals. They may accomplish these ambitions through carrying out their business processes more effectively. Hence it is important to consider such processes and look for ways in which they can be improved.